The Educational Consequences of Language Proficiency for Young Children - Yuxin Yao; Asako Ohinata; Jan C. van Ours (Institute for the Study of Labor (IZA), 2016)
This paper studies the educational consequences of language proficiency by investigating the relationship between dialect-speaking and academic performance of 5-6 year old children in the Netherlands. We find that dialect-speaking has a modestly negative effect on boys' language test scores. In addition, we study whether there are spillover effects of peers' dialect-speaking on test scores. We find no evidence for spillover effect of peers' dialect-speaking. The test scores of neither Dutch-speaking children nor dialect-speaking children are affected by the share of dialect-speaking peers in the classroom.
Keywords: J24; I2; 330; dialect-speaking; test scores; spillover effects; language; academic performance